Kinematic Analysis of Transplanting Mechanisms of Selected Mechanical Rice Transplanters - Thomas, E. V.; Kumar, Uttam (Journal of Agricultural Engineering, 2018)
Self-propelled rice transplanting machines were commercially produced and used in Japan. Countries like Thailand, Bangladesh, India, Sri Lanka and Pakistan are still carrying out researches for development of mechanical rice transplanter suitable for their countries. Most power-operated transplanters use two-dimensional four-bar linkage mechanism in their planting unit with the transplanting finger an extension of the coupler link. Design of power-operated planting mechanisms involves a process of analytical synthesis to analyse the path of motion and velocity of finger at the point of picking of the seedling and at the point of planting. Link dimensions are modified until a suitable mechanism is obtained. This paper summarizes some of the planting designs for development of rice transplanters.